Feasibility analysis of drill bit tracking using seismic while drilling technique - Sun, Baichun; Zhou, B.; Bona, Andrej; Pevzner, Roman (CSIRO, 2012)
Check-shot survey measures the first arrival time with a known depth receiver in borehole to assess formation velocity. This information can be used in correlation with sonic log and surface seismic products for adjustment of interpretation. Check-shot survey can also be implemented with seismic-while-drilling using drill bit noise as the source. This differs from usual check-shot survey as source is in the borehole. It provides a real time, cost saving, and safe measurement. Check-shot survey needs a known receiver depth, thus velocity can be obtained by fixed wave travel path and the measured first arrival time. However, in seismic-while-drilling (SWD), drill bit position can vary a lot from vertical drilling to deviated drilling. To address this issue, we present a method that finds the location of the source and estimates the velocity of the formation at the same time. Using a synthetic model, with medium receiver offsets, this method shows good estimation of the drill bit depth location and formation velocity in a layered Earth model.